Hermeneutic Study: The Meaning of Lyric From Kebalai Singing In Rote Ndao Society (Jurnal Seni Musik, 2022)
Traditional art through music, dance and even traditional rituals becomes a symbol and identity of the community because it is a reflection of collective thoughts and also regional solidarity. Kebalai is a dance danced by the people of Rote and is very famous. The kebalai does not only contain dances but also songs in the form of rhymes which are performed together in every event, from big events such as when. The poetry uses the Rote regional language and the meaning of each song is different. This makes researchers interested in looking at oral literature through the songs from the balai and efforts to document the meaning of the poem from the kebalai entitled "Susue Lain" which means brotherly love. This study uses a hermeneutic study according to Ricoeur. The research method uses qualitative methods and literature studies, data collection techniques. Data collection in this study is by observing and unstructured interviews. The results of the Kebalai research are a dance that is often danced together by the people of Rote, in every event or activity that exists. The conclusion in this study is that Kebalai is a performing art, which in the way of interpreting it uses poetry to convey messages.